Perbandingan Def-t Berdasarkan Jenis Kelamin Anak TK Saraswati III Denpasar - Made Dea Herawati; Putu Dinda Maheswari; Ni Putu Dita Kristiana Putri; Ni Luh Dyah Puspa Sari; Ni Luh Eka Purnamayanti; Ni Luh Gede Erlita Cahyanti; Yudha Rahina; I Gusti Ayu Ratih Pramesti (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2026)
One of the most common dental and oral health problems in early childhood is dental caries. This can affect children's comfort, chewing ability, and quality of life. In addition, this situation can have an impact on their growth and development. The purpose of this study was to assess the dental health status and dmft index of children aged between 5 and 6 years at Saraswati III Kindergarten in Denpasar. This study used a quantitative descriptive approach involving 31 children (13 boys and 18 girls) in class B4 at Saraswati III Kindergarten. The examination was conducted directly on the primary teeth using the def-t recording format.The results showed that the average def-t index for boys was 3.46 (moderate category) and for girls was 2.78 (moderate category). In percentage terms, 18.9% of boys had caries in their primary teeth, while only 13.4% of girls did. The results of this study indicate that children at Saraswati III Kindergarten in Denpasar, especially those in class B4, still have a high incidence of dental caries, with a higher average def-t score among boys. These results indicate that better dental health education, proper tooth brushing habits, and regular dental check-ups in the school environment from preschool age are needed to reduce the incidence of caries and improve children's oral health.